Student-athletes' dual commitment to school and sport: Compatible or conflicting?. (January 2021) - O'Neil, Liam; Amorose, Anthony J.; Pierce, Scott
Abstract: There is general agreement that for collegiate student-athletes to thrive in academics and athletics these individuals must develop and maintain quality commitments to both school and sport throughout college. Yet, limited research has investigated student-athletes' concurrent negotiation of their discrete commitments to school and sport, and its consequences for these individuals' academic, athletic, and general lives. The purpose of the present study was threefold: (a) identify distinct profiles representing collegiate students-athletes' dual commitment to school and sport, (b) detect whether these dual commitment profiles demonstrated compatibility versus conflict, and (c) examine the relationships between dual commitment profiles and student-athletes' academic, athletic, and general life outcomes. A sample of 248 NCAA Division I student-athletes ( Mage  = 19.87 years, SD  = 1.33 years) completed measures of commitment, engagement, and burnout in school and sport, as well as global psychological well-being indices (i.e., life satisfaction and subjective vitality). Using latent profile analyses, results supported a four-profile solution comprising dual commitment profiles with unique configurations of enthusiastic (EC) and constrained (CC) commitment to school and sport: Weak CC-Dominant: School/Strong EC-Dominant: Sport ( n  = 43), Weak CC-Dominant: School/Strong CC-Dominant: Sport ( n  = 71), Moderate Commitment: School & Sport ( n  = 91), and Strong EC-Dominant: School & Sport ( n  = 43). Dual commitment profiles characterized by enthusiastic-dominant commitment patterns were associated with higher levels of school/sport engagement and global psychological well-being, as well as lower levels of school/sport burnout. Overall, our findings established that collegiate student-athletes are tied to school and sport for various reasons and speak to a potential need for enhanced support networks and services catered to student-athletes' academic role in the United States. Highlights: We investigated the interaction between collegiate student-athletes' two distinct commitments to school and sport. Four dual commitment profiles emerged characterized by unique configurations of two commitment dimensions to school and sport. Dual commitment profiles exhibited varying degrees of compatibility and conflict between school and sport commitments. Enthusiastic-dominant commitment patterns were linked to elevated school and sport engagement, and global well-being. Constrained-dominant commitment patterns were linked to elevated school and sport burnout.